Spherical copper-chromium composite metal oxide combustion rate catalyst and preparation method thereof
The spherical copper-chromium composite metal oxide combustion rate catalyst was prepared by co-precipitation method and spray drying process, which solved the problems of irregular morphology and wide particle size distribution of traditional catalysts, and improved the catalytic efficiency and the stability of the propellant combustion rate.
Patent Information
- Application Number
- CN202211706496.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-29
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2042-12-29
AI Technical Summary
Traditional transition metal oxides have problems such as irregular morphology, wide particle size distribution and impurities, resulting in a decrease in catalytic activity, affecting the combustion speed of the propellant, and unstable quality between batches.
Through co-precipitation method and spray-drying ultrafine spherical granulation process, a copper-chromium composite metal oxide combustion rate catalyst with higher spherical shape, adjustable particle size and narrow particle size distribution was prepared.
The catalytic efficiency of the copper-chromium oxide combustion rate catalyst is significantly improved, the combustion rate and pressure index of the propellant are improved, and the stability of product quality between batches is ensured.
Smart Images

Figure CN116212886B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of burning rate catalysts and relates to a spherical copper-chromium composite metal oxide burning rate catalyst and a preparation method thereof. Background Art
[0002] As the requirements of air defense tactical missiles in terms of attacking high-speed, high-maneuverability aircraft and the use environment continue to increase, higher and higher requirements are placed on the performance of solid propellants, requiring propellants to have high energy, high burning rate and other characteristics. Usually, the burning rate of the propellant is increased by adding a certain mass ratio of burning rate catalyst.
[0003] Composite transition metal oxides are widely used in propellants due to their high catalytic activity and anti-migration properties. However, due to the irregular morphology, wide particle size distribution and impurities of commercially available and existing process-prepared transition metal oxides, the catalytic activity is reduced, affecting the burning rate of the propellant; and due to the unstable quality between batches, the consistency of the quality of the engine charge products and the stability of the burning rate of the propellant cannot be ensured between batches. Summary of the invention
[0004] The purpose of the present invention is to overcome the above-mentioned defects and provide a spherical copper-chromium composite metal oxide combustion rate catalyst and a preparation method thereof, which solves the technical problems that traditional transition metal oxides have irregular morphology, wide particle size distribution and impurities, resulting in reduced catalytic activity and affecting the burning rate of the propellant. The present invention prepares a copper-chromium composite metal oxide combustion rate catalyst with higher sphericity, adjustable particle size, narrow particle size distribution and higher catalytic efficiency.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention relates to a method for preparing a burning rate catalyst applicable to butyl hydroxyl and azide polyether composite solid propellants, and in particular to a method for preparing a spherical copper-chromium composite oxide burning rate catalyst, which can improve the sphericity and uniformity of particle size distribution of the copper-chromium composite metal oxide burning rate catalyst, significantly improve the catalytic efficiency of the copper-chromium oxide burning rate catalyst, and effectively improve the preparation process of the propellant. 2+ With Cr 3+ of water-soluble salt solution, and control the Cu 2+ / Cr 3+The molar ratio is 3.0 to 4.0, and then an ammonium carbonate aqueous solution is added dropwise while stirring, and a blue-green precipitate is obtained by a coprecipitation method, and then a spherical copper-chromium composite metal oxide combustion rate catalyst is prepared by spray drying ultrafine spherical granulation, high-temperature calcination and other processes. The obtained spherical copper-chromium composite metal oxide combustion rate catalyst is added to a butyl hydroxyl and polyether composite solid propellant according to a certain mass ratio, which can effectively increase the combustion rate of the propellant, reduce its pressure index, and improve the process performance of the propellant preparation. The present invention is characterized in that by controlling the copper-chromium ion concentration ratio, solution pH value, furnace temperature, calcination temperature and other conditions, a copper-chromium composite metal oxide combustion rate catalyst with higher sphericity, adjustable particle size, narrow particle size distribution and higher catalytic efficiency is prepared, and the preparation method can be directly used for large-scale industrial production of the combustion rate catalyst.
[0007] A method for preparing a spherical copper-chromium composite metal oxide combustion rate catalyst comprises:
[0008] S1 prepares Cu in the reactor 2+ With Cr 3+ A mixed water-soluble salt solution;
[0009] S2 to Cu under stirring conditions 2+ With Cr 3+ Add an aqueous solution of ammonium carbonate dropwise to the mixed water-soluble salt solution, and continue stirring after the addition is complete to obtain a blue-green precipitate;
[0010] S3: preparing the blue-green precipitate into a suspension, spray drying the suspension to obtain a spherical copper-chromium composite metal oxide catalyst precursor, i.e., basic copper-chromium carbonate powder;
[0011] S4 calcines the basic copper chromium carbonate powder to obtain a spherical copper chromium composite metal oxide combustion rate catalyst.
[0012] Furthermore, in step S1, Cu 2+ With Cr 3+ The mixed aqueous salt solution consists of Cu 2+ Aqueous salt solutions and Cr 3+ A water-soluble salt solution is mixed to obtain;
[0013] Cu 2+ The water-soluble salt solution is one or more of Cu(NO3)2 or CuSO4; Cr 3+ The water-soluble salt solution is one or more of Cr(NO3)3 or CrCl3.
[0014] Furthermore, in step S1, Cu 2+ With Cr 3+ In a mixed aqueous salt solution of Cu 2+The concentration of Cr is 1mol / L~2mol / L, 3+ The concentration is 0.4mol / L~0.8mol / L;
[0015] Cu 2+ With Cr 3+ The molar ratio is 2.6 to 3.5.
[0016] Further, in step S2, the concentration of the aqueous ammonium carbonate solution is 2 mol / L to 3 mol / L;
[0017] Under stirring conditions, Cu 2+ With Cr 3+ When an aqueous ammonium carbonate solution is added dropwise to a mixed water-soluble salt solution, the dropping process is 90 min to 120 min. After the dropping is completed, stirring is continued for 30 min to 60 min to obtain a blue-green precipitate.
[0018] Furthermore, in step S2, the pH value of the solution obtained after the dropwise addition of the aqueous ammonium carbonate solution is 5.8 to 7.4.
[0019] Furthermore, in step S3, the solution obtained in step S2 is filtered and washed to obtain a blue-green precipitate; the blue-green precipitate is prepared into a suspension of 0.04 to 0.07 kg / L.
[0020] Further, in step S3, the method of spray drying the suspension is:
[0021] S3.1 Add the suspension dropwise to the feed port of the spray dryer through a peristaltic pump while stirring;
[0022] S3.2 The dryer of the spray dryer atomizes the suspension into droplets, which are directly sprayed into the tower of the spray dryer to obtain basic copper chromium carbonate powder;
[0023] The temperature of the tower furnace is 110℃~130℃.
[0024] Furthermore, in step S4, the method for calcining the basic copper chromium carbonate powder is:
[0025] The basic copper chromium carbonate powder is placed in a muffle furnace and calcined at 650°C to 750°C for 3h to 5h.
[0026] A spherical copper-chromium composite metal oxide combustion rate catalyst is obtained by adopting the preparation method of the spherical copper-chromium composite metal oxide combustion rate catalyst.
[0027] Furthermore, the average particle size of the spherical copper-chromium composite metal oxide combustion rate catalyst is 15 μm to 25 μm.
[0028] Compared with the prior art, the present invention has at least one of the following beneficial effects:
[0029] (1) The preparation method of the present invention has the advantages of simple process flow, high production capacity, no use of organic solvents or organic reactants, low production cost, controllable product quality, etc., and is suitable for industrial batch production;
[0030] (2) The spherical copper-chromium composite metal oxide combustion rate catalyst prepared by the present invention has the advantages of controllable particle size, narrow particle size distribution range, high sphericity and high catalytic efficiency;
[0031] (3) The spherical copper-chromium composite metal oxide prepared by the present invention has higher crystallinity and can effectively improve the catalytic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a SEM image of the spherical copper-chromium composite metal oxide precursor obtained in Example 1 of the present invention;
[0033] Figure 2 This is a SEM image of the spherical copper-chromium composite metal oxide obtained in Example 1 of the present invention;
[0034] Figure 3 This is a particle size distribution diagram of the spherical copper-chromium composite metal oxide precursor obtained in Example 1 of the present invention;
[0035] Figure 4 This is a particle size distribution diagram of the spherical copper-chromium composite metal oxide obtained in Example 1 of the present invention;
[0036] Figure 5 (a) is the XRD pattern of the spherical copper-chromium composite metal oxide obtained in Example 1 of the present invention; Figure 5 (b) is the XRD pattern of ordinary copper-chromium composite metal oxide. DETAILED DESCRIPTION
[0037] The following detailed description of the present invention will make the features and advantages of the present invention more clear and explicit.
[0038] The word "exemplary" is used exclusively herein to mean "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as preferred or advantageous over other embodiments. Although various aspects of the embodiments are shown in the drawings, the drawings are not necessarily drawn to scale unless otherwise noted.
[0039] The present invention aims to solve the problems of a copper-chromium composite oxide burning rate catalyst preparation process used in butyl hydroxyl and polyether composite solid propellants, such as a complex process flow, uncontrollable product morphology, and a wide particle size distribution. The present invention provides a method for preparing a copper-chromium composite metal oxide burning rate catalyst powder with high production capacity, simple process, sphericity, and narrow particle size distribution. The method of the present invention can obtain a burning rate catalyst with high catalytic activity, stable particle size between batches, and high sphericity, thereby meeting the high reliability requirements of solid missile engines.
[0040] The technical solution of the present invention is to first synthesize the precursor by coprecipitation, then obtain the spherical intermediate product by spray drying and granulation, and finally obtain the spherical copper-chromium composite metal oxide combustion rate catalyst by high temperature calcination. The specific steps are:
[0041] A. Prepare Cu in the reactor 2+ With Cr 3+ A mixed aqueous salt solution of Cu 2+ With Cr 3+ The mixed water-soluble salt solution contains Cu with a molar concentration of 1 mol / L to 2 mol / L. 2+ 、0.4mol / L~0.8mol / L Cr 3+ A water-soluble salt solution, controlling the Cu / Cr molar ratio to be 2.6 to 3.5; in this step, controlling the Cu / Cr molar ratio is beneficial to the formation of the target product;
[0042] B. prepare an ammonium carbonate aqueous solution with a molar concentration of 2 mol / L to 3 mol / L;
[0043] C. Add the ammonium carbonate aqueous solution dropwise to the Cu 2+ Cr 3+ The dropping process is about 90min to 120min, and the pH value of the reaction solution is controlled to be 5.8 to 7.4 by adjusting the concentration and the amount of sodium carbonate solution added; in this step, controlling the pH value is conducive to the normal progress of the reaction, and too high or too low pH will cause side reactions, thereby affecting the yield of the target product;
[0044] D. After the reaction is completed, continue stirring for 30 to 60 minutes to obtain a blue-green precipitate, filter and wash it, and then prepare it into a 0.04 to 0.07 kg / L suspension;
[0045] E. slowly dripping the mixture to the feed port of the spray dryer through a peristaltic pump while stirring, and then atomizing the mixture into droplets through the atomizer of the dryer, and spraying the droplets directly into the tower body, and controlling the temperature of the drying furnace to 110° C. to 130° C. to obtain a dry spherical copper-chromium composite metal oxide precursor product, i.e., basic copper-chromium carbonate powder; in this step, controlling the temperature of the drying furnace is conducive to controlling the evaporation rate of the liquid, and thus controlling the particle size of the powder;
[0046] F. calcining the basic copper chromium carbonate powder at 700°C for 3h to 5h to obtain a spherical copper chromium oxide combustion rate catalyst with an average particle size of 15μm to 25μm. In this step, controlling the calcination temperature is beneficial to maintaining the crystal form of the powder;
[0047] The Cu 2+ The water-soluble salt solution is preferably one of Cu(NO3)2, CuSO4 or a mixed solution; Cr 3+ The water-soluble salt solution is preferably one of Cr(NO3)3, CrCl3 or a mixed solution.
[0048] More preferably, Cu 2+ The water-soluble salt solution is selected as Cu(NO3)2; Cr 3+ The water-soluble salt solution is Cr(NO3)3; the dosage of copper nitrate and chromium nitrate can be adjusted appropriately according to the different contents of copper and chromium.
[0049] Preferably, the aqueous ammonium carbonate solution is added dropwise to the Cu 2+ Cr 3+ The solution was added dropwise for 110 min and the pH value of the reaction solution was controlled to be 6.0-7.0.
[0050] Preferably, when the pH value of the reaction solution is low, the amount of ammonium carbonate can be appropriately increased;
[0051] Preferably, after the reaction is completed, stirring is continued for 40 min to 60 min;
[0052] Preferably, the temperature of the drying furnace is controlled to be 110°C to 120°C;
[0053] Preferably, the basic copper chromium carbonate powder is calcined at 700° C. for 4 hours.
[0054] The present invention also evaluates the effect of spherical copper-chromium composite metal oxide on the combustion performance of PBT propellant. Spherical copper-chromium composite metal oxide is directly added to the PBT propellant formula according to a certain mass ratio, and the addition amount (mass percentage) is usually 0.2% to 1.2%; the formula solid content is about 83%; the binder system is PBT / BQ; the plasticizer is A3; and the solid filler is AP / Al.
[0055] Improving the morphology quality of the composite metal oxide burning rate catalyst and reducing its particle size distribution range is one of the key technologies for increasing and stabilizing the burning rate of propellants, and is also an important factor in improving the quality stability of engine charge products between batches. Compared with the existing preparation process, the present invention does not require special synthesis environment and process requirements, and only needs three steps to synthesize a spherical composite metal oxide burning rate catalyst. It has the characteristics of simple synthesis method and simple process, and is suitable for engineering batch production.
[0056] The present invention is further described below in conjunction with the embodiments.
[0057] Example 1
[0058] According to the ratio, weigh 2.84kg of copper nitrate and 1.36kg of chromium nitrate, add them to 10L of deionized water to dissolve; weigh 1.38kg of ammonium carbonate and dissolve it in 5L of deionized water. Add the ammonium carbonate aqueous solution dropwise to the copper-chromium ion mixed solution while stirring, and control the dropping process for 110min. Continue stirring for 40min after the addition is completed. The pH value is measured to be 6.5 after the stirring is completed. After the reaction is completed, filter the precipitate and wash the precipitate with deionized water for 3-5 times.
[0059] The precipitate is dispersed in a deionized water solution to prepare a 0.07 kg / L suspension, which is added dropwise to the feed port of a spray dryer while being ultrasonically stirred. The temperature of the drying furnace is controlled to be 110° C. After drying, a spherical copper-chromium composite metal oxide precursor powder with an average particle size of 15 μm to 25 μm, i.e., basic copper-chromium carbonate powder, is obtained, which is blue-green in color.
[0060] Finally, the obtained spherical powder was calcined at 700° C. for 4 hours to obtain a spherical copper-chromium composite metal oxide combustion rate catalyst powder with an average particle size (D50) of 15 μm to 25 μm, which was dark brown in color.
[0061] Take a small amount of basic copper chromium carbonate powder and place it in distilled water. Ultrasonic dispersion is performed in an ultrasonic cleaner for 5 minutes. Drop it on a copper sample table and observe the particle morphology and particle size by scanning electron microscopy. Figure 1 As shown in the figure, the obtained basic copper chromium carbonate powder presents a regular spherical shape under an electron microscope and is evenly dispersed in the medium, and the average particle size of the powder is between 15μm and 25μm.
[0062] The same procedure was used to obtain the SEM image of spherical copper-chromium composite metal oxide powder, as shown in Figure 2 As shown in the figure, the obtained spherical copper-chromium composite metal oxide powder presents a regular spherical shape under an electron microscope and is evenly dispersed in the medium, and the average particle size of the powder is between 15 μm and 25 μm.
[0063] Take a small amount of basic copper chromium carbonate powder and place it in distilled water, and ultrasonically disperse it in an ultrasonic cleaner for 5 minutes. Use Malvern 2000 analyzer to test its particle size and distribution. Figure 3 As shown in the figure, it can be seen that the particle size of most basic copper chromium carbonate powders is between 15μm and 25μm.
[0064] The same procedure was used to obtain the particle size and distribution diagram of copper-chromium composite metal oxide powder, as shown in Figure 4 As shown in the figure, it can be seen that the particle size of most copper-chromium composite metal oxide powders is between 15μm and 25μm.
[0065] The obtained copper-chromium composite metal oxide powder was subjected to X-ray diffraction analysis, and the results were as follows: Figure 5 (a). As shown in the figure, in the X-ray diffraction pattern, the strongest diffraction peaks appear at around 36° and 39°, corresponding to the (0 0 2) and (1 1 1) crystal planes of CuO. The diffraction peaks at 32°, 46° and 49° also correspond to other crystal planes of CuO. The diffraction peaks at around 31°, 42° and 56° correspond to different crystal planes of Cu(Cr2O4). In addition, there are other weaker diffraction peaks corresponding to different crystal planes of copper-chromium composite metal oxides. Analysis Figure 5 (b), the strongest diffraction peaks also appear at around 36° and 39°, corresponding to the two crystal planes of CuO; the diffraction peaks at other positions also correspond to different crystal planes of CuO and Cu(Cr2O4), but they are not obvious. Figure 5 (b) is the XRD pattern of the common copper-chromium composite metal oxide obtained by directly calcining the precipitate, Figure 5 (b) Compared with Figure 5 (a) The baseline is stable, the diffraction peak intensity is sharper, the signal-to-noise ratio is higher, and the diffraction peak is more obvious, indicating that the powder has better crystallinity and more accurate image.
[0066] 0.8% spherical copper-chromium composite metal oxide and ordinary copper-chromium composite metal oxide were added to PBT propellant, and the burning rate of the propellant was tested. The test results are shown in Table 1. As can be seen from the table, the burning rate of the propellant with the spherical copper-chromium composite metal oxide prepared by the method is 14.4 mm / s, which is 0.6 mm / s higher than that of the propellant with the ordinary copper-chromium composite metal oxide.
[0067] Table 1 Comparison results of burning rate test of PBT propellant with 0.8% spherical copper-chromium composite metal oxide and ordinary copper-chromium composite metal oxide
[0068]
[0069] Example 2
[0070] According to the ratio, weigh 3.68kg of copper nitrate and 1.40kg of chromium nitrate, add them to 10L of deionized water to dissolve; weigh 1.38kg of ammonium carbonate and dissolve it in 5L of deionized water. Add the ammonium carbonate aqueous solution to the copper-chromium ion mixed solution while stirring, and control the dropping process for 110min. Continue stirring for 40min after the addition is completed. The pH value is measured to be 6.2 after the stirring is completed. After the reaction is completed, filter the precipitate and wash the precipitate with deionized water for 3 to 5 times.
[0071] The precipitate is dispersed in a deionized water solution to prepare a 0.07 kg / L suspension, which is added dropwise to the feed port of a spray dryer while being ultrasonically stirred. The temperature of the drying furnace is controlled to be 110° C. After drying, a spherical copper-chromium composite metal oxide precursor powder with an average particle size of 15 μm to 25 μm, i.e., basic copper-chromium carbonate powder, is obtained, which is blue-green in color.
[0072] Finally, the obtained spherical powder was calcined at 700° C. for 4 hours to obtain a spherical copper-chromium composite metal oxide combustion rate catalyst powder with an average particle size (D50) of 15 μm to 25 μm, which was dark brown in color.
[0073] Example 3
[0074] According to the ratio, weigh 51.1kg of copper nitrate and 24.3kg of chromium nitrate, add them into 180L of deionized water to dissolve; weigh 24.8kg of ammonium carbonate and dissolve them in 90L of deionized water. Add the ammonium carbonate aqueous solution dropwise to the copper-chromium ion mixed solution while stirring, and the dropping process lasts for 110min. Continue stirring for 60min after the addition is completed. The pH value is measured to be 6.5 after the stirring is completed. After the reaction is completed, filter the precipitate and wash the precipitate with deionized water for 3 to 5 times.
[0075] The precipitate is dispersed in a deionized water solution to prepare a 0.07 kg / L suspension, which is added dropwise to the feed port of a spray dryer while being ultrasonically stirred. The temperature of the drying furnace is controlled to be 120° C. After drying, a spherical copper-chromium composite metal oxide precursor powder with an average particle size of 15 μm to 25 μm, i.e., basic copper-chromium carbonate powder, is obtained, which is blue-green in color.
[0076] Finally, the obtained spherical powder was calcined at 700° C. for 4 hours to obtain a spherical copper-chromium composite metal oxide combustion rate catalyst powder with an average particle size (D50) of 15 μm to 25 μm, which was dark brown in color.
[0077] Example 4
[0078] According to the ratio, weigh 66.2kg of copper nitrate and 25.2kg of chromium nitrate, add them into 180L of deionized water to dissolve; weigh 24.8kg of ammonium carbonate and dissolve them in 90L of deionized water. Add the ammonium carbonate aqueous solution dropwise to the copper-chromium ion mixed solution while stirring, and the dropping process lasts for 110min. Continue stirring for 60min after the addition, and the pH value is measured to be 6.2 after the stirring. After the reaction is completed, filter the precipitate and wash the precipitate with deionized water for 3 to 5 times.
[0079] The precipitate is dispersed in a deionized water solution to prepare a 0.07 kg / L suspension, which is added dropwise to the feed port of a spray dryer while being ultrasonically stirred. The temperature of the drying furnace is controlled to be 120° C. After drying, a spherical copper-chromium composite metal oxide precursor powder with an average particle size of 15 μm to 25 μm, i.e., basic copper-chromium carbonate powder, is obtained, which is blue-green in color.
[0080] Finally, the obtained spherical powder was calcined at 700° C. for 4 hours to obtain a spherical copper-chromium composite metal oxide combustion rate catalyst powder with an average particle size (D50) of 15 μm to 25 μm, which was dark brown in color.
[0081] The invention provides a method for preparing a spherical copper-chromium composite metal oxide combustion rate catalyst. The invention has the following advantages: on the one hand, the reactant is a metal water-soluble salt solution, which can be directly dissolved in water, and the preparation process route is simple, the production capacity is high, and the harshness of the catalyst preparation conditions is reduced; on the other hand, the product quality between batches is relatively stable and the product quality is controllable; secondly, the sample sphericity is relatively complete, the particle size distribution is uniform, and the crystallinity is better; thirdly, the spherical copper-chromium composite metal oxide combustion rate catalyst not only has a higher catalytic efficiency, but also can improve the preparation process of the propellant, and ensure the quality stability of the engine charge product between batches.
[0082] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
[0083] The contents not described in detail in the specification of the present invention belong to the common knowledge of those skilled in the art.
Claims
1. An application of a spherical copper-chromium composite oxide combustion rate catalyst, characterized in that: Spherical copper-chromium composite oxide is used as a rapid combustion catalyst of PBT propellant. The spherical copper-chromium composite metal oxide is directly added into the PBT propellant formula in an amount of 0.2% to 1.2% by mass, and the solid content of the formula is 83%. The binder system is PBT / BQ; the plasticizer is A3; the solid filler is AP / Al, and the average particle size of the spherical copper-chromium composite metal oxide combustion rate catalyst is 15μm to 25μm, and the composition contains CuCr2O4 and CuO. The preparation method of the spherical copper-chromium composite metal oxide combustion rate catalyst comprises: S1 preparing Cu in a reaction kettle 2+ With Cr 3+ Mixed water-soluble salt solution of Cu 2+ With Cr 3+ The molar ratio is 2.6~3.5; S2 to Cu under stirring conditions 2+ With Cr 3+ Add an aqueous solution of ammonium carbonate dropwise to the mixed water-soluble salt solution, and continue stirring after the addition is complete to obtain a blue-green precipitate; S3: preparing the blue-green precipitate into a suspension, spray drying the suspension to obtain a spherical copper-chromium composite metal oxide catalyst precursor, i.e., basic copper-chromium carbonate powder; S4 calcines the basic copper chromium carbonate powder to obtain a spherical copper chromium composite metal oxide combustion rate catalyst.
2. The use according to claim 1, characterized in that: In step S1, Cu 2+ With Cr 3+ The mixed aqueous salt solution consists of Cu 2+ Aqueous salt solutions and Cr 3+ A water-soluble salt solution is mixed to obtain; Cu 2+ The water-soluble salt solution is one or more of Cu(NO3)2 or CuSO4; Cr 3+ The water-soluble salt solution is one or more of Cr(NO3)3 or CrCl3.
3. The use according to claim 1, characterized in that: In step S1, Cu 2+ With Cr 3+ In a mixed aqueous salt solution of Cu 2+ The concentration is 1mol / L ~2mol / L, Cr 3+ The concentration is 0.4mol / L ~0.8mol / L.
4. The use according to claim 1, characterized in that: In step S2, the concentration of the aqueous ammonium carbonate solution is 2 mol / L to 3 mol / L; Under stirring conditions, Cu 2+ With Cr 3+ When an aqueous ammonium carbonate solution is added dropwise to a mixed water-soluble salt solution, the dropping process is 90 min to 120 min. After the dropping is completed, stirring is continued for 30 min to 60 min to obtain a blue-green precipitate.
5. The use according to claim 4, characterized in that: In step S2, the pH value of the resulting solution after the dropwise addition of the aqueous ammonium carbonate solution is 5.8-7.
4.
6. The use according to claim 1, characterized in that: In step S3, the solution obtained in step S2 is filtered and washed to obtain a blue-green precipitate; the blue-green precipitate is prepared into a suspension of 0.04-0.07 kg / L.
7. The use according to claim 6, characterized in that: In step S3, the method of spray drying the suspension is: S3.1 Add the suspension dropwise to the feed port of the spray dryer through a peristaltic pump while stirring; S3.2 The dryer of the spray dryer atomizes the suspension into droplets, which are directly sprayed into the tower body of the spray dryer to obtain basic copper chromium carbonate powder; the temperature of the tower body furnace is 110℃~130℃.
8. The use according to claim 6, characterized in that: In step S4, the method for calcining the basic copper chromium carbonate powder is: placing the basic copper chromium carbonate powder in a muffle furnace and calcining it at 650° C. to 750° C. for 3 h to 5 h.
Citation Information
Patent Citations
CO-SCR low-temperature efficient non-noble metal oxide catalyst and preparation method thereof
CN112138665A